Jewelers of stars: the planetary (Journal of Parents and Teachers, 2014)
Learning about history of planetariums and the educative opportunities that they offer are the aims of this article. More than two thousand years ago, the firmament was already being observed and people at that time wanted to reproduce it to study it. 400 years ago when Galileo pointed to the sky with a telescope and in the 20th century Bauersfeld built the first planetarium, similar to the ones we have now. Engineering and creativity at the service of everyone, especially because school programs offered in planetariums deal with the necessities of every school year.
Keywords: family and school; planetariums; school programs; astronomy